Hemodynamic parameters and reproductive outcome after intracytoplasmic sperm injection and fresh embryo transfer in patients undergoing oocyte retrieval with general anesthesia using fentanyl, remifentanil or alfentanil – A randomized clinical trial - Farnoush Farzi; Marzieh Mehrafza; Ali Mirmansouri; Ziba Zahiri Sorouri; Zahra Atrkar Roushan; Azadeh Raoufi; Reyhane Shalkohi; Sajedeh Samadnia; Ahmad Hosseini (Taiwanese Journal of Obstetrics & Gynecology, 2019)
Objective: Anesthesia for assisted reproductive technology is very important to provide less stressful and painful environment for patients, with minimal side effects on oocytes. In the present study, we aimed to evaluate hemodynamic parameters, recovery time and intracytoplasmic sperm injection (ICSI) outcome among patients underwent anesthesia with fentanyl, remifentanil or alfentanil. Material and methods: This randomized double-blinded clinical trial was conducted in patients undergoing anesthesia for transvaginal ultrasound guided oocyte retrieval (TUGOR). Patients were randomly allocated to alfentanil (A; 15 μg/kg), fentanyl (F; 1.5 μg/kg) or remifentanil (R; 1.5 μg/kg) groups. Results: Three hundred forty patients were assessed for eligibility and randomized for transvaginal oocyte retrieval following general anesthesia and 105 were lost to follow up. No statistically significant differences were noted among groups regarding basic characteristics. Although, time to respond to verbal command was significantly different among groups (A: 1.99 ± 1.64, F: 2.56 ± 1.72, R: 1.78 ± 1.34, P = 0.014). There were no significant differences among groups with respect to the first and second postoperative pain intensity, patient satisfaction, pre-induction and post-induction systolic and diastolic blood pressure (BP). Terminal systolic (A: 101.61 ± 9.15, F: 105.29 ± 12.61, R: 102 ± 12.91, P = 0.01) and diastolic (A: 59.97 ± 9, F: 65.63 ± 9.13, R: 63.69 ± 11.01, P = 0.003) BP was significantly different among groups. The fertilization rate was significantly different among groups (A: 51.6%, F: 54.4%, R: 62.2%, P = 0.018). Implantation rate, biochemical and clinical pregnancy rate was similar among groups. Conclusions: The results of present study demonstrated that all three opioids have the same efficiency, in regards to patient satisfaction and pregnancy outcome. However, Anesthesia with alfentanil compared with fentanyl and remifentanil, seems to be inferior for TUGOR due to higher effect on fertilization rate and less hemodynamic stability. Registration number: IRCT201410258677N4. Keywords: Alfentanil, Fentanyl, Remifentanil, General anesthesia, Intracytoplasmic sperm injections